2022
DOI: 10.2147/ppa.s354705
|View full text |Cite
|
Sign up to set email alerts
|

Finalization and Validation of Questionnaire and Algorithm of SPUR, a New Adherence Profiling Tool

Abstract: Purpose The SPUR (Social, Psychological, Usage and Rational) Adherence Profiling Tool is a recently developed adaptive instrument for assessing key patient-level drivers for non-adherence. This study describes the SPUR questionnaire’s finalization and psychometric evaluation. Patients and Methods Data were collected through an online survey among patients with type 2 diabetes included by general practitioners and diabetologists in France. The survey included four questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The proposed SPUR model framework 31 and initial model development 32 process have been reported previously. Furthermore, psychometric properties for populations based in the US 33 and France 34 have been reported, in addition to a UK-based cohort of patients living with type 2 diabetes (VMATT2) 35 that produced a more concise SPUR tool – SPUR-27. This study sought to develop a predictive model of early readmission and general admission risk using the SPUR-27 tool as a holistic PROM of medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed SPUR model framework 31 and initial model development 32 process have been reported previously. Furthermore, psychometric properties for populations based in the US 33 and France 34 have been reported, in addition to a UK-based cohort of patients living with type 2 diabetes (VMATT2) 35 that produced a more concise SPUR tool – SPUR-27. This study sought to develop a predictive model of early readmission and general admission risk using the SPUR-27 tool as a holistic PROM of medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The four key domains of MA termed Social, Psychographic, Usage, and Rational comprise the 45-item measure and can be used to evaluate individual factors and behaviours related to non-adherence. 21,22 Recently, a shorter 27-item version of the SPUR tool (SPUR-27) was validated for patients living with type 2 diabetes in a UK study by Wells et al 23 The revised 27-item model demonstrated greater reliability than the original SPUR-45 tool as well as significant correlations with objective and PROMs of MA in addition to socio-clinical factors such as body mass index (BMI) and income. The psychometric properties of the tool, as well as its relationship to patient socio-clinical factors, have yet to be evaluated in patients living with COPD.…”
Section: Introductionmentioning
confidence: 99%